2013
DOI: 10.1371/journal.pone.0072926
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Mesenchymal Stromal Cells and MSC Conditioned Medium in Amyotrophic Lateral Sclerosis (ALS) - In Vitro Evidence from Primary Motor Neuron Cultures, NSC-34 Cells, Astrocytes and Microglia

Abstract: Administration of mesenchymal stromal cells (MSC) improves functional outcome in the SOD1G93A mouse model of the degenerative motor neuron disorder amyotrophic lateral sclerosis (ALS) as well as in models of other neurological disorders. We have now investigated the effect of the interaction between MSC and motor neurons (derived from both non-transgenic and mutant SOD1G93A transgenic mice), NSC-34 cells and glial cells (astrocytes, microglia) (derived again from both non-transgenic and mutant SOD1G93A ALS tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 71 publications
1
47
0
Order By: Relevance
“…Such an anti‐inflammatory/neuroprotective effect was recently corroborated ex vivo using MSCs derived from mice transgenic for mutant superoxide dismutase 1 (G93A‐SOD1 mice), the mouse model for amyotrophic lateral sclerosis. MSCs, which have neuroprotective effects in this disease, apparently affect neuroinflammation in G93A‐SOD1 mice not only through release of CX3CL1 but also by stimulating the release of this chemokine by astrocytes and upregulating the expression of its receptor, CX3CR1, in G93A‐SOD1 microglia . Similarly, human MSCs were shown to express CX3CL1 upon infusion in rats with acute focal cerebral ischemia and to induce CX3CL1 expression by resident cells …”
Section: Effects Of Mscs On Innate Immunitymentioning
confidence: 97%
“…Such an anti‐inflammatory/neuroprotective effect was recently corroborated ex vivo using MSCs derived from mice transgenic for mutant superoxide dismutase 1 (G93A‐SOD1 mice), the mouse model for amyotrophic lateral sclerosis. MSCs, which have neuroprotective effects in this disease, apparently affect neuroinflammation in G93A‐SOD1 mice not only through release of CX3CL1 but also by stimulating the release of this chemokine by astrocytes and upregulating the expression of its receptor, CX3CR1, in G93A‐SOD1 microglia . Similarly, human MSCs were shown to express CX3CL1 upon infusion in rats with acute focal cerebral ischemia and to induce CX3CL1 expression by resident cells …”
Section: Effects Of Mscs On Innate Immunitymentioning
confidence: 97%
“…On the basis of recent literature and our own in vitro studies, MSCs appear suitable to provide substantial benefit to ALS patients (reviewed in Ciervo, Ning, Jun, Shaw, & Mead, ; Sun et al, ). They can differentiate to multiple mesodermal lineages including bone, cartilage, and adipose tissue and can furthermore be induced to differentiate into different cell types of endoderm and neuroectoderm lineages, therefore bearing also the potential for neuronal and glial differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have shown that MSC-CM accelerates wound healing [30,31], promotes liver regeneration [32] and improves cardiac function following myocardial infarction [33]. The neuroprotective effects of MSC were demonstrated to be more efficient through the paracrine effects (by using its CM) compared to the cell-cell contact manner [14]. This study was targeted to elucidate the effects of MSC-CM on microglial activation to examine its immunomodulation role before proceeding to identify the ‘functional' substances (due to the complexity and diversity of MSC-CM [32,33,34]) .…”
Section: Discussionmentioning
confidence: 99%
“…MSC are increasingly gaining importance for their immunomodulatory functions [11]. They have been shown to inhibit various immune cells and have the potential for moderating inflammation in various cell types, including T cells, B cells, dendritic cells, natural killer cells, neutrophils, astrocytes and activated microglia [12,13,14]. Moreover, MSC show potential for immunotherapy for neurodegenerative diseases as they have been shown to modulate microglial activation [15,16].…”
Section: Introductionmentioning
confidence: 99%